Risk factors for the recurrence of atrial fibrillation after catheter ablation: a meta-analysis - Gonghao Li; Yanli Zhao; Zhongxing Peng; Yunfeng Zhao (The Egyptian Heart Journal)
Abstract Background The rate at which atrial fibrillation (AF) patients experience a return of symptoms after catheter ablation is significant, and there are multiple risk factors involved. This research intends to perform a meta-analysis to explore the risk factors connected to the recurrence of AF in patients following catheter ablation. Methods The PubMed, Cochrane Library, WOS, Embase, SinoMed, CNKI, Wanfang, and VIP databases were explored for studies from January 1, 2000 to August 10, 2021, and research meeting the established inclusion requirements was chosen. Two authors separately gathered details regarding the study structure. The strength of the link between various risk factors and AF returning after CA was evaluated using odds ratios. All statistical evaluations were conducted with RevMan5.3 software. Results In total, 44 articles and 62,674 patients were included. The OR for AF recurrence in patients with diabetes was 2.04 compared with the reference group (95% CI 1.51–2.76, p < 0.00001); that of lower left ventricular ejection fraction was 1.38 (95% CI 1.25–1.52, p < 0.00001); that of female was 1.34 (95% CI 1.18–1.52, p < 0.00001); that of increased age was 1.03 (95% CI 1.02–1.04, p < 0.00001); that of persistent AF was 1.72 (95% CI 1.58–1.87, p < 0.00001); that of AF duration over 2 years was 1.17 (95% CI 1.08–1.26, p < 0.00001); that of increased left atrial diameter (LAD) was 1.12 (95% CI 1.08–1.17, p < 0.00001); that of larger left atrial volume index (LAVi) was 1.02 (95% CI 1.01–1.03, p < 0.00001); that of higher hs-CRP was 1.19 (95% CI 1.04–1.36, p = 0.04); that of early recurrence (ER) was 3.22 (95% CI 2.74–3.77, p < 0.00001); and that of long ablation duration was 1.00 (95% CI 0.98–1.02, p = 0.72). Heterogeneity and slight publication bias were observed for each factor. Conclusions Evidence indicates that diabetes, low left ventricular ejection fraction, being female, older age, longer duration of atrial fibrillation, elevated high-sensitivity C-reactive protein levels, large left atrial dimension, large left atrial volume index, persistent atrial fibrillation, and exercise rehabilitation are factors that increase the chances of getting atrial fibrillation again after catheter ablation. However, the length of the ablation procedure does not relate to the recurrence of AF.